Visual acuity performance with cosmetic contact lenses prescribed by unlicensed vendor / Amat Al-Azizah Ariffin - Ariffin, Amat Al-Azizah (Faculty of Health Sciences, 2015)
Purpose: To measure the visual acuity performance under high and low contrast visual acuity with cosmetic soft contact lens prescribed by unlicensed vendors among UiTM students. Materials and methods: High and low contrast visual acuity was measured in eleven cosmetic soft contact lens wearers and eleven clear soft contact lens wearers. The participants were asked to read the logMAR chart at 4m under different contrast level of visual acuity which was high contrast visual acuity at 100% and low contrast visual acuity at 25% and 10%. Results: Cosmetic soft contact lens wearer had statistically significant reduced for both high and low contrast visual acuity (P<0.01) than clear soft contact lens wearer. The visual acuity of cosmetic soft contact lens wearer for high contrast level 100% was 6/6 and low contrast level 25% and 10% were 6/7.5 and 6/9 respectively. Three lines of visual acuity was reduced at lower contrast level of visual acuity. The visual acuity for clear soft contact lens wearer for high contrast level 100% was 6/6 and low contrast level 25% and 10% was 6/7.5. Conclusion: Cosmetic soft contact lens wear appear to induce a reduction in visual acuity performance especially at low contrast of visual acuity in which 25% and 10%. Cosmetic soft contact lens wearer should be informed about the effects on optical quality and visual function.